Aripiprazole compared with placebo for auditory verbal hallucinations in youth with borderline personality disorder: Protocol for the VERBATIM randomized controlled trial. Issue 6 (28th January 2019) - Chanen, Andrew M.; Betts, Jennifer; Jackson, Henry; McGorry, Patrick; Nelson, Barnaby; Cotton, Sue M.; Bartholomeusz, Cali; Jovev, Martina; Ratheesh, Aswin; Davey, Christopher; Pantelis, Christos; McCutcheon, Louise; et al.
Abstract : Aim: Up to half of patients with borderline personality disorder report auditory verbal hallucinations that are phenomenologically indistinguishable from those in schizophrenia, occur early in the course of the disorder, and are enduring, distressing and disabling. In clinical practice, this symptom is widely assumed to be unresponsive to treatment with antipsychotic medication and early intervention is rarely offered. The Verbal Experiences Response in Borderline personality disorder to Aripiprazole TrIal Medication (VERBATIM) study aims to be the first controlled trial to investigate the effectiveness of conventional pharmacotherapy for this symptom in this patient group. Method: VERBATIM is a 12‐week, triple‐blind, single‐centre, parallel groups randomised controlled trial, with a 27‐week follow‐up period. Participants between the ages of 15 and 25 years receive either aripiprazole or placebo daily, commencing at 2 mg and increasing to 10 mg by day 15. Further dose escalations (up to 30 mg) may occur, as clinically indicated. This trial was prospectively registered with the Australian and New Zealand Clinical Trials Registry ACTRN12616001192471 on 30/08/2016. Results: The primary outcome is severity of auditory verbal hallucinations assessed using the Psychotic Symptom Rating Scale. Secondary outcomes include the severity of general psychopathology, borderline personality pathology, social and occupational functioning and change in brain resting state connectivity. The primary endpoint is week 12 and secondary endpoint is week 39. Conclusion: The results will inform treatment decisions for individuals with borderline personality disorder who present with auditory verbal hallucinations.